Implementasi Mesin Pres Sepatu Sistem Pneumatik Semi Otomatis dan Perbaikan Manajemen untuk Meningkatkan Produktivitas Industri Kecil Sepatu Banjarsari - Saiful Anwar; Eko Wahjudi; Yunus (Jurnal Pengabdian Pada Masyarakat, 2022)
IMPLEMENTATİON OF SEMİ-AUTOMATİC PNEUMATİC SYSTEM SHOE PRESS MACHİNE AND MANAGEMENT IMPROVEMENT TO INCREASE PRODUCTİVİTY OF BANJARSARİ SMALL SHOE INDUSTRY. The purpose of this PKM is to help resolve the priority problems of Syaifullah's small Banjarsari shoe industry, namely: 1) low quality and quantity of sole and upper gluing production, and 2) weak production management and financial management. To solve these problems, it is carried out through the implementation of a semi-automatic pneumatic system shoe press machine and improvement of production management and financial management. The method of implementing PKM to solve partner problems is carried out in stages: a) establishing partnerships with small shoe industry entrepreneurs, b) determining partner priority problems, c) designing machines, d) machine manufacturing, e) assembly, f) function testing, g) training machine operation and maintenance, h) machine delivery and implementation, i) management improvement training and assistance, and j) periodic monitoring. The result of this PKM is a semi-automatic pneumatic system shoe press machine that is effective and efficient and the management of small shoe industry partners has improved. The implementation of this shoe press machine is able to increase the quality of the adhesive strength and the quantity of production of leather shoe gluing in the small industry of partner shoes 3 times greater than the manual gluing process. The implementation of production management and financial management of the small shoe industry of partners has been well managed